Relasi Manusia dengan Alam Semesta: Sebuah Kajian Literatur Islam: Anisa Zulfa Maqfirah*, Sudarmadi Putra - Anisa Zulfa Maqfirah; Sudarmadi Putra (Samudra Publisher, 2024)
Humans are sovereign as caliphs of the earth because, as God's creatures, they differ from other species in their specificity. Humans need the means, the universe and everything in it, to actualize the meaning of the caliphate. From the perspective of the Koran, this article aims to examine more deeply the ideas about nature and humanity and their relationship. Apart from that, this article also attempts to discuss human ethics towards the environment; humans are responsible for protecting and preserving the environment. The author will use a qualitative descriptive method in studying this problem by examining the verses of the Koran that are relevant to the relationship between humans and the environment or universe. From this study, it was concluded that the relationship between humans and the natural environment is interdependent; on the one hand, humans can utilize nature for the benefit of their lives, but at the same time humans have the responsibility to care for and preserve the universe. This is possible because humans are caliphs, one of whose three things is carrying out the mandate to protect nature from damage, as well as having ethics towards nature and the environment where humans live.